La formation initiale des enseignants du premier degré à l’inclusion scolaire des élèves en situation de handicap : le point de vue de formateurs d’INSPE - Marine Dintrich; Caroline Hache; Caroline Ladage (Éducation et Socialisation)
The aim of this article is to present the results of a research on the perception of INSPE trainers about the construction of initial training programs for primary school teachers and, more specifically, about the lessons and resources made available to trainee teachers to learn how to implement the school inclusion of pupils with disabilities in ordinary classes. Carried out with a didactic approach, our research highlights the predominance of personal relationships to the issues raised by inclusive schooling over institutional relationships which are struggling to be constructed and disseminated.